DISCIPLINE THE PARTICIPANT IN FOLLOWING THE EQUALITY PROGRAM IN UPTD C PACKAGE FOR SKB PEKANBARU - Nurhidayati '; Jasfar Jas Jas; Murni Baheram Baheram (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This study was based on the low level of discipline equality program participants in UPTD c package for SKB Pekanbaru. The problem of this research is how high the discipline of learning programs in UPTD equality c SKB Pekanbaru. The aim of this study was to determine the level of discipline of participants in the program in UPTD c ksesetaraan package for SKB Pekanbaru. The population in this study of 53 participants and a sample study of 33 people taken by using random sampling techniques. Data collection instruments, namely a questionnaire with 54 statements and after the trial lived 45 valid statement to be made in the research instrument. Data analysis through quantitative descriptive analysis. Results obtained from the calculation results based performance indicators of the ability to comply with the level of discipline-time high of 92.11% and a low level of discipline as much as 3.87%, indicating persistent in carrying out the duties of discipline high level of 89.96% and a low level of discipline by 7 , 41%, mengerjaan indicator and complete the task on time with high level of discipline at 97.37% and the low level of discipline at 2.17%, the indicators do not procrastinate 98.75% and low discipline level of 1.25% to the value and obey the norms that discipline the level higher by 96.77% and low discipline level of 3.2%. Keywords: Disicipline, Discipline participant, Program Package C